When Age Matters: Patterns of Participative and Communicative Practices in the Czech Republic - Alena Macková; Hana Macháčková; Jakub Macek; Jan Šerek (Communication Today, 2025)
After a long history, research on the relation between participative and communicative practices was revived in the late 1990s because of the proliferation of new media. New studies have taken into account both online and offline participation and the ability of new media to provide citizens with easier access to information and a broader repertoire of actions. In this article, which is based on a representative survey of the adult Czech population and a survey of Czech adolescents, we address participative and communicative practices as intertwined sets that are typically preferred by certain groups of citizens. As media-related and political practices usually vary due to generational and historical experience, the aim is to discover whether people with similar generational backgrounds and with similar repertoires of action manifest similar sets of communication practices, i.e. similar media ensembles. Hence, we build this study on the assumption that the political-and media-related agencies are structured by historical experience as well as by biographical experience linked with life-cycle phases. Using cluster analysis, we focus on the various participative and communicative practices employed by three distinct adult generational groups and by contemporary adolescents, all of whom experienced the process of socialization in their own specific historical contexts.